Pharmacokinetics of Intraperitoneal Vancomycin and Amikacin in Automated Peritoneal Dialysis Patients With Peritonitis - Falbo dos Reis, Pâmela; Barretti, Pasqual; Marinho, Laudilene; Balbi, Andre Luís; Awdishu, Linda; Ponce, Daniela (Frontiers in Pharmacology, 2021)
Objective: The study aimed to evaluate vancomycin and amikacin concentrations in serum and dialysate for automatic peritoneal dialysis (APD) patients. Methods: A total of 558 serum and dialysate samples of 12 episodes of gram-positive and 18 episodes of gram-negative peritonitis were included to investigate the relationship between vancomycin and amikacin concentrations in serum and dialysate on the first and third days of treatment. Samples were analysed 30 min, 120 min and 48h after intraperitoneal administration of vancomycin in peritonitis caused by grm-positive agents and 30 min, 120 min and 24h after intraperitoneal administration of amikacin in peritonitis caused by gram-negative agents. Vancomycin was administered every 72h and amikacin once a day. Target therapeutic concentration of amikacin was 25–35 mg/l at the peak moment and 4–8 mg/l at the trough moment; and after 48 h for vancomycin, 15–20 mg/l at the trough moment. Results: For peritonitis caused by gram-negative agents, at the peak moment, therapeutic levels of amikacin were reached in dialysate in 80.7% of patients with evolution to cure and in 50% of patients evaluated as non-cure (p=0.05). Peak plasma concentrations were subtherapeutic in all samples in the cure and the non-cure group. At the trough moment, therapeutic concentrations were present in 74.4% of the cure group and 71.4% of the non-cure group (p=1). Regarding vancomycin and among gram-positive agents, therapeutic levels were reached at the peak moment in 94% of the cure group and 6% of the non-cure group (p=0.007). After 48 h, 56.8% of the cure group had a therapeutic serum concentration whereas for the non-cure group it was only 33.3% (p=0.39). Conclusions:The assessment of amikacin and vancomycin concentrations in dialysate and plasma illustrates that, at the peak moment, therapeutic concentrations of amikacin are required in the dialysate for therapeutic success of peritonitis caused by gram-negative agents, whereas plasma vancomycin concentrations appear to be more important for curing peritonitis by gram-positive agents. Therefore, it is important to study the pharmacodynamics of these drugs for a better understanding of therapeutic success.